Southern lights [compact disc, unabridged] : a novel - Steel, Danielle (Brilliance Audio, 2009)
Set in the Deep South, Danielle Steel's Southern Lights unfolds the story of a mother and daughter both commencing new and separate lives, one in corporate Manhattan, fighting to put a serial killer behind bars, and the other in sultry Charleston, reconnecting with the father she's barely known.